Perancangan Aplikasi Media Sosial TeiTei - Diofavian Rafif Chairulsyah; Claudio Nehemia Panggabean; Aditya Dwi Wibowo; Umniy Salamah (FORMAT, 2025)
Digital transformation has driven the need for social media platforms that can provide simple, personal, and effective interactions. However, many existing applications tend to offer complex features that are less relevant to user needs. This research aims to design and develop TeiTei, a web-based social media application that emphasizes ease of use, convenience, and interactivity. This research includes identifying user needs, designing a user-friendly interface using the CSS Bootstrap framework, developing a PHP-based system with the Laravel framework, and managing the database using MySQL. In addition, a search algorithm was implemented to improve the efficiency of finding other users on the platform. The results of this research produced a web-based social media application prototype that can meet user needs through an intuitive interface design and relevant features. The implementation of search algorithms also adds value by expanding users' social networks. This research is expected to make a significant academic contribution to the development of social media applications, as well as serve as a reference for similar studies aimed at enhancing digital social interaction experiences.